Counseling on The Importance of Maintaining Women's Reproductive Health - Safitri, Riri (JURNAL PENGMAS KESTRA (JPK), 2024)
Maintaining women's reproductive health behavior is something that is very important for every woman from childhood, adolescence, to adulthood. This is because the female reproductive organs are organs that function as a place for menstrual blood to exit, a place for fetal development and sexual intercourse. Many reproductive health problems can arise from not maintaining women's reproductive health, one of which is cervical cancer. Therefore, the author conducted counseling on the importance of maintaining women's reproductive health to PKK mothers in Pasar VI Kualanamu Village with the aim of increasing the knowledge of PKK mothers about the importance of maintaining women's reproductive health, so that later the information conveyed is expected to have a positive impact on the village about maintaining women's reproductive health, where it is known that PKK mothers are organizations that work directly with residents, especially women in the village. During the counseling, the method used was the lecture method. With 28 counseling participants. Counseling was carried out in several stages, including the activity process stage and the evaluation stage. This counseling activity was carried out on May 8, 2024 at the multipurpose building of Pasar 6 Kualanamu Village, Beringin District. From the results obtained, it is known that the percentage value of achievement in the final questionnaire of participants after counseling is mostly in the high to moderate range classification. From these data, it shows that the counseling carried out in Pasar 6 Kualanamu Village was able to increase the knowledge of counseling participants consisting of PKK mothers, with this it is hoped that the information conveyed will have a positive impact on the village about maintaining women's reproductive health, where it is known that PKK mothers are an organization that works directly with residents, especially women in the village.